Public Perception of the Development of Café Business and its Affect on the Sustainable Conservation District Images : The Case of Braga, Bandung - Indonesia - Bunga Sakina (Engineering, MAthematics and Computer Science (EMACS) Journal, 2020)
Conservation district has a vital role in supporting a sustainable city. One form of revitalization strategy in conservation district is to incorporate new functions into old buildings, such as café business. The involvement of stakeholders is required to achieve proper implementations of sustainable revitalization, and one of them is the café visitors as the users. The purpose of this study was to find out public perceptions of the development of café business and how café buildings affect the image of Braga conservation district. Several cafés in Braga District of Bandung City were chosen as the object of this research study. This mixed qualitative-quantitative research collected data using the online questionnaire method, unstructured interviews and direct observation. Data analysis was performed quantitatively using distribution analysis. The results of the study showed that the majority of café visitors who are millennial generations visited the café for social interactions. in addition, it was also found that the physical aspects of the café building were also the reason they were attracted to visit the café. Although many cafés arise, public could still feel the image of the Braga conservation district. The café that was considered the most representative of the district's image was a café that retains its original appearance, brings the concept of locality and provide setbacks. The results of this study can be input for the government and the private sector as a direction for the development of sustainable conservation districts. Keywords:  conservation district, sustainable, revitalization, café, public perception, conservation district images